A new ternary composite steel rebar coating for enhanced corrosion resistance in chloride environment. (21st February 2022) - Harilal, Manu; George, R.P.; Albert, Shaju.K.; Philip, John
Highlights: A novel ternary composite coating for steel rebars in a chloride environment is developed. Coating consists of fly ash, nanoparticles, and inhibitor. New coating significantly improved the corrosion protection of rebars. Salt spray results showed a two-order reduction in corrosion rate in coated sample. Long term electrochemical measurements showed a higher Rct value for coated rebar. Abstract: This work reports a novel ternary cement polymer composite coating (CPFNIC) consisting of fly ash, nanoparticles, and inhibitor with enhanced corrosion protection for steel rebars in a chloride environment. Electrochemical impedance spectroscopy (EIS) measurements, polarization curves, salt spray test, scanning electron microscopy (SEM), and Confocal Laser Scanning Microscopy (CLSM) were used to understand the corrosion protection mechanism and for characterization of corrosion products. The results show that the new coating significantly delayed the onset of corrosion on rebars in aggressive chloride environments due to the synergistic contributions from the additives used. The electrochemical studies (open circuit potential and corrosion current) indicate a significantly improved corrosion performance of CPFNIC as compared to uncoated rebars. The potentiodynamic polarization results of CPFNIC coated rebars showed high corrosion potential, low corrosion current density, three order higher polarization resistance, and two-order lower corrosion rate than the uncoated rebar. The EIS measurements showed a significantly higher charge transfer resistance for the CPFNIC as compared to the uncoated rebar. The visual inspection and weight loss measurements in salt spray and chemical resistance tests of CPFNIC coated rebars corroborated its improved resistance in chloride environment. Our results suggest the benefits of ternary composite cementitious coating on rebars in enhancing the corrosion protection.